Engineering-Oriented Modeling for Thermal Behaviors of 18650 Li-ion Batteries. (May 2017) - Cheng, Ximing; Shi, Nan; Li, Yang; Wang, Shouqun
Abstract: Because temperature takes a significant effect on both degradation and safety of Li-ion batteries, thermal models are often used to analyze their temperature distribution with cycling under varying operation conditions. In engineering, micro-element-based numerical models can be built by commercial software of thermal analysis, the heat generation rate of which was obtained only by a constant resistor as the internal resistance of a battery. In this paper, both surface temperature and state-of-charge of a battery are fed back to get model parameters interpolated to elaborate an oriented-application heat generation rate. This enhanced technique was developed in a routine and integrated into the thermo-electrical model in the commercial software Fluent ® . Compared to the 1D and 2D thermal models, the thermo-electrical model produced the best simulated temperature of one 18650 Li-ion battery.